Clinicians’ Views on the Need for Cultural Adaptation of Intervention for Children with ADHD from the Ultraorthodox Community - Anat Golos; Risa Mor; Orit Fisher; Adi Finkelstein (Occupational Therapy International)
Culture is a core context within occupational therapy, with a recent literature emphasizing the importance of cultural competence, as well as culturally sensitive assessment and intervention. The recent literature has indicated the efficacy of the Cognitive-Functional intervention (Cog-Fun) for children with ADHD among the general Israeli population, yet no studies to date have examined the necessity of cultural adaptations for minority groups. The current study examines the necessity of adapting the intervention protocol and process to the Ultraorthodox (UO) population, as perceived by occupational therapists. The study included 28 occupational therapists certified to use the Cog-Fun intervention, who reported using this approach with UO children. Participants responded to an online questionnaire developed for this study, regarding characteristics of the UO population and necessary adaptions to the Cog-Fun intervention process and protocol. Findings were analyzed using descriptive statistics and qualitative content analysis. Results of the study point to the necessity of addressing various features of the UO community, including daily routines and habits, cultural values, knowledge regarding ADHD, and accessibility of information. Participants also reported a need to adapt the graphic content of the intervention materials. The qualitative data expanded on the perceptions of the participants through four main themes: (a) knowledge regarding ADHD diagnosis and intervention; (b) perceptions and attitudes regarding ADHD diagnosis and medication; (c) factors affecting communication between the OT, parents, and teachers; and (d) adapting the intervention protocol to habits, routines, and lifestyle of UO families. This study has direct implications for therapists utilizing the Cog-Fun with UO children and may also provide insights relevant to occupational therapists using other treatment approaches with children from this culture, as well as other minority or traditional groups. Furthermore, this study may serve as an important addition to the limited literature describing cultural adaptations of evidence-based interventions.